Multidisciplinary Approaches & Strategies for Soil & Water Conservation Programme - Tejwani, K.G. (Journal of Soil and Water Conservation, 2022)
Soil and water conservation (SWC) is very old and is practised extensively by both the shifting cultivators as well as settled agriculturists. For example, strictly speaking the traditional long fallow shifting cultivation in the humid and sub-humid tropics of Asia, Pacific and Africa is the most appropriate response of the farmers to the local agro- ecological conditions (such as hilly landscape, high to very high prevalent rainfall, low in- herent soil fertility and the fact that most of the plant nutrients are tied up in the forest).